Geochemical and Sm–Nd isotopic characteristics of the Late Archaean-Palaeoproterozoic Dhanjori and Chaibasa metasedimentary rocks, Singhbhum craton, E. India: Implications for provenance, and contemporary basin tectonics - De, S.; Mazumder, Rajat; Ohta, T.; Hegner, E.; Yamanda, K.; Bhattacharyya, T.; Chiarenzelli, J.; Altermann, W.; Arima, M. (Elsevier BV, 2015)
In significant contrast to other cratonic blocks of India, the Singhbhum cratonic successions record continuous depositional record from the Palaeoarchaean to Mesoproterozoic. Although the sedimentary facies characteristics and mode of stratigraphic sequence building of the Dhanjori and Chaibasa Formations are well known, sedimentary geochemistry, provenance and tectonic milieu of deposition of these two formations are hitherto unknown. The current manuscript presents geochemical and Sm–Nd isotopic data from the Dhanjori and Chaibasa Formations for the first time and combine previous sedimentological data with the goal to expand the framework for understanding the depositional and tectonic setting of these two formations. The Sm–Nd isotopic data for the Chaibasa clastics is unambiguous with respect to provenance. Average ɛNd (t = 2.2 Ga) = −0.8 ± 1.0 and average Nd model age (TDM) = 2.51 ± 0.08 Ga with average 147Sm/144Nd ratios = 0.1114 ± 0.0041 for phyllites and quartzites indicate an extremely homogeneous source signature consistent with a late Archaean “juvenile” crustal provenance, possibly a dominantly upper crustal provenance. The Sm–Nd isotopic data from the older Dhanjori Formation also indicate broadly similar provenance as comparable lithologies in the younger Chaibasa Formation. Our Sm–Nd isotopic data is entirely consistent with the previous sedimentological data and confirms a terrestrial, rift-dominated tectonic setting for the Dhanjori Formation (proximal sources, poorly mixed provenance) and a marginal marine to offshore setting for the more homogeneous Nd isotopic signature of the Chaibasa Formation (distal sources, well mixed provenance).